RISE OF SINGLE PARENT FAMILIES AND ITS IMPACT ON SOCIETY - Vikas Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The phenomenon known as "single parenthood" is one that has been around for as long as there have been people on Earth. According to Dowd Nancy in (1997), a single parent is a parent who takes on the most of the day-to-day responsibilities for parenting the kid or children while not cohabitating with their spouse or partner. This definition applies to a parent who is not married.The process of socialising children is essential to the continued existence of any society. Many people believe that the family unit is the single most important factor in the process of socialisation, particularly for children. Parents have a significant role in the process of instilling strong underlying moral, spiritual, social, physical, and cognitive standards in their children throughout the majority of cultural contexts. The upbringing of children is characterised by a strict adherence to routines and norms (Santrock, 2002).The extended family model of child raising that was common in Africa before to the advent of industrialization and globalisation has been significantly altered as a result of these two societal shifts. The rapid social change that comes along with globalisation has caused disruptions in the lives of families (Olaleye, Y.L et al, 2010). Many of the traditional customs and rites that were formerly passed down from generation to generation and carefully preserved are on the verge of extinction. Our nation's values and advantages, which were formerly seen to be the core pillars of our society, have changed and outgrown those ideals and advantages as contemporary culture has progressed. In this day and age, behaviour that was once considered unacceptable is rapidly becoming the norm.